Impact of Covid-19 on Alzheimer Patients: How One Crisis Worsens the Other - Rubal Gupta (Tehran University of Medical Sciences, 2023)
The coronavirus has caused chaos in the lives of many people in our society, one of which is the disruption of our daily routines. For those with Alzheimer's disease or those who care for someone with Alzheimer's disease, the coronavirus has the potential to be lethal. The COVID-19 epidemic has wreaked havoc on people with Alzheimer's disease (AD) and other dementias. Corona virus illness, which is characterised by severe acute respiratory syndrome, has arisen as a substantial comorbidity. The immediate physical effects of Covid-19 have been widely investigated, but little is known regarding the long-term consequences. The authors investigate the symptoms of Alzheimer's disease and how it worsens COVID-19, as well as the mechanisms at work at all levels, from biological to social. COVID-19's impact on brain function and viral entry pathways into the brain, as well as the factors that lead to COVID-19-related cognitive impairment, were also examined. The researchers looked on the prevalence and mortality of COVID-19 in Alzheimer's patients, as well as the impact of the pandemic on uninfected dementia patients and Alzheimer's disease management